Canal of Nuck cyst: surgical management and lymphatic preservation in three cases - C. Eretta; F. Di Pumpo; C. Bianchi; N. Gorji; M. Moroni; C. Feleppa (Veins and Lymphatics)
The canal of Nuck cyst is a rare but clinically relevant pathology, often mistaken for inguinal hernias or other soft tissue anomalies. It results from the incomplete obliteration of the processus vaginalis during fetal development. In this report, we describe three cases of adult women with this condition and highlight diagnostic approaches, surgical treatment, and, crucially, the intraoperative strategy for lymphatic preservation. We emphasize the relevance of venous and lymphatic anatomy in surgical planning and propose a refined diagnostic and therapeutic framework for this under-recognized pathology.